Kesadaran Lingkungan dalam Perubahan Iklim - Sheila Nurul Fajar; Dede Lilis Chaerowati (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Film is one of the communication media that can be used to convey or provide information to the wider community. Along with its development, films have a considerable impact on the wider community. This happens because films have their own way of conveying information through interesting stories. One of the films that is deliberately produced to convey information is the film called